The Role of Business Development Strategies and Capital Access Challenges in Driving Green Investment in Supply Chains and Islamic Financial Markets - Alifiani Nurul Aisyah; Tika Sari Erawati (Start-up and Financial Technology, 2025)
Objective: This study aims to analyze the role of business development strategies and access to capital in driving green investment in Islamic supply chains and financial markets and identify policy challenges to create an ecosystem conducive to economic and environmental sustainability. Research Design & Methods: This research employed a qualitative approach with thematic analysis of the literature and case studies, to identify patterns of equity in green investment and sustainable finance. Findings: The research found that green investments support corporate sustainability and performance through innovation strategies such as blockchain technology and green supply chain collaboration, although challenges related to capital access and business awareness remain key barriers. Implications & Recommendations: Collaboration between governments and the private sector is essential to drive the adoption of green investments, with governments providing supportive policies and companies investing in green technologies, and the potential of technologies such as blockchain to improve transparency across sectors is worth exploring further. Contribution & Value Added: This research is expected to provide deeper insights into how green investments can serve as a tool to achieve broader sustainability goals without neglecting the needs and rights of local communities.